Analisa dan Perancangan Sistem Rekrutmen Online (E-Recruitment) Berbasis Web pada PT Bravo Security Indonesia - Ivan Royanto Hutabarat; Jay Idoan Sihotang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
In this globalization era, the need for security is increasing, in addition to data or information security but also a sense of physical security, therefore security guard services are still needed to protect certain places or regions. In this case, PT. Bravo Security Indonesia as a security guard distributor company, requires many prospective security guards to be able to work in various public or private agencies. The purpose of this study is to design an online-based recruitment system that can be used by applicants as well as the personnel department at PT. Bravo Security Indonesia. The expected analysis and design is to be able to analyze the information or data requirements for the recruitment process aimed at prospective security guards who want to apply for this company. The design uses the waterfall model, whose modeling requires Need Analysis (Recruitment Analysis), System Design (System Design), Program Code Making (Coding), Implementation and Testing (Testing), and Support and Maintenance (Support and Maintenance). The results are in the form of an online recruitment system specifically for the personnel department, because personnel will have the information needed to be able to assess applicants before they are called to proceed to the direct interview session. In addition to simplifying the process of recruiting security guards, this system is also expected to make data collection of new security guards easier and integrated with the system, and suggestions for the future are that the system can be developed to recruit employees other than security guards.